PALI DALAM AKTIVITAS SEHARI-HARI SUKU DAYAK NGAJU DESA MANTANGAI HULU KABUPATEN KAPUAS (Pali in the Daily Activities of Dayak Ngaju Village of Exgai Hulu Kapuas Regency) - Lastaria Lastaria; Lailatul Fithriyah Azzakiyah (SAWERIGADING, 2022)
Dayak Ngaju tribe is a tribe rich in ancestral heritage so that it has a culture that is quite adhered to by the owner of the culture itself. However, the culture is only inherited from oral to oral so that the form of cultural writing of the Dayak Ngaju community is very minimal. Pali or pamali is also included in the oral tradition of Dayak Ngaju which is almost extinct due to the development of the times. However, if you investigate further that behindthe word "pali" or abstinence there are educational values contained in it. The method used in this study is an exploratory method used to explore various events related to activities or activities that are prohibited by the Dayak Ngaju tribe. As for data collection techniques by way of direct observation to the field as well as interviews with community leaders and surrounding youth as comparison data. Based on the results of the study there are several abstinences classified into the prohibition of the Dayak Ngaju tribe, namely: (1)  pali related to oneself and others; (2)  pali related to the behavior towards the parents, related to the ethics and behavior of a person towards the older person must respect each other so that bad luck will be experienced by the person who violates it; (3)  palis  related to homework; and (4)  palis  related to supernatural beings.